2018
DOI: 10.15171/apb.2018.060
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Activity of an Isolated Fraction from Rhinella schneideri Poison

Abstract: Purpose: Rhinella schneideri is a toad found in many regions of the South America. The poison of the glands has cardiotoxic effect in animals and neuromuscular effects in mice and avian preparation. The purpose of this work was to identify the toxin responsible for the neuromuscular effect in avian and mice neuromuscular preparation.Methods: The methanolic extract from R. schneideri poison was fractioned by reversed phase HPLC. The purity and molecular mass were determined by LC/MS mass spectrometry. Chick biv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…schneideri poison-induced neuromuscular blockade in avian preparations has been associated to a presynaptic mechanism of action, which is characterized by an absent of muscle responses to exogenous ACh and KCl, low creatine kinase (CK) release and no significant morphological damage, indicating that the functionality of postsynaptic nicotinic receptors and muscle membrane integrity were not affected by the poison (Rostelato-Ferreira et al, 2011). Recently, Rostelato-Ferreira et al, (2018 reported the purification and pharmacological characterization of a non-enzymatic presynaptic active toxin (fraction 20) among a total of thirty-two fractions isolated from R. schneideri poison, with molecular mass determined in 730.6 Da; under low concentration, this toxin induces neuromuscular facilitation followed by complete inhibition of muscle twitches recorded in BC preparations (Rostelato-Ferreira et al, 2018), mimicking the neuromuscular effect produced by R. schneideri poison in the same experimental model (Rostelato-Ferreira et al, 2011). The neuromuscular activity of R. schneideri poison has also been investigated in mouse phrenic nerve diaphragm (PND) preparation, in which producing progressive improvement of the acetylcholine release characterized by an increase in the frequency of miniature end-plate potentials and quantal content of evoked end-plate potentials, with no observation of neuromuscular failure (Rostelato-Ferreira et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…schneideri poison-induced neuromuscular blockade in avian preparations has been associated to a presynaptic mechanism of action, which is characterized by an absent of muscle responses to exogenous ACh and KCl, low creatine kinase (CK) release and no significant morphological damage, indicating that the functionality of postsynaptic nicotinic receptors and muscle membrane integrity were not affected by the poison (Rostelato-Ferreira et al, 2011). Recently, Rostelato-Ferreira et al, (2018 reported the purification and pharmacological characterization of a non-enzymatic presynaptic active toxin (fraction 20) among a total of thirty-two fractions isolated from R. schneideri poison, with molecular mass determined in 730.6 Da; under low concentration, this toxin induces neuromuscular facilitation followed by complete inhibition of muscle twitches recorded in BC preparations (Rostelato-Ferreira et al, 2018), mimicking the neuromuscular effect produced by R. schneideri poison in the same experimental model (Rostelato-Ferreira et al, 2011). The neuromuscular activity of R. schneideri poison has also been investigated in mouse phrenic nerve diaphragm (PND) preparation, in which producing progressive improvement of the acetylcholine release characterized by an increase in the frequency of miniature end-plate potentials and quantal content of evoked end-plate potentials, with no observation of neuromuscular failure (Rostelato-Ferreira et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These components, especially those bufadienolides and bufotoxins, have been considered potential therapeutic tools for exhibiting cancer inhibitory activity (Meng et al, 2009), apoptosis suppressive action (Qi et al, 2010) and antimicrobial activity (Tempone et al, 2008). The paratoid gland secretion and their components, e.g., non-enzymatic presynaptic active toxin (730.6 Da) isolated from R. schneideri poison (Rostelato-Ferreira et al, 2018), can induce neurotoxicity characterized by suppression of the motor acetylcholine release (Rostelato-Ferreira, Dal Belo, Cruz-Höfling, Hyslop, & Rodrigues-Simioni, 2011;Rostelato-Ferreira, Dal Belo, Leite, Hyslop, & Rodrigues-Simioni, 2014;Rostelato-Ferreira et al, 2018), including cardiotoxicity consisted in arrhythmia and ventricular failure mostly by antagonizing Na + / K + ATPase of cardiomyocytes (Toledo & Jared, 1995;Sakate & Oliveira, 2000;Gadelha, Lima, Batista, Melo, & Soto-Blanco, 2014;Leal et al, 2020). R. marinus and R. vulgaris are responsible for causing the most cases of envenomation in domestic animals (Sakate & Oliveira, 2000;Sakate & Oliveira, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The preparations were stabilized for 20 min prior to testing the fractions that were added in a fixed concentration of 10 µg/mL. The potential influence of RIPS and its fractions on postsynaptic cholinergic nicotinic receptors (indicative of neurotoxicity) and skeletal muscle fibers (indicative of myotoxicity) was assessed by comparing the contractile responses to 110 µM ACh and 24 mM KCl, respectively, before (basal responses) and after incubation with the secretion and fractions [90]. Muscle contractile responses were recorded for 120 min after the addition of RIPS or fractions.…”
Section: Chick Biventer Cervicis Preparationmentioning
confidence: 99%
“…Poisoned dogs showed mydriasis, nystagmus and opisthotonus [17,18]. Some studies suggest mechanisms of interaction between bufadienolides and the neuromuscular junction [19,20], causing blockage of synaptic transmission [17,21]. Molecules such as resibufogenin and cinobufagin demonstrated actions on voltagegated potassium channels and resibufogenin also in the voltagegated sodium channels [22,23].…”
Section: Introductionmentioning
confidence: 99%